PELATIHAN DAN PENDAMPINGAN PENERAPAN MEDIA AJAR DIGITAL WORDWALL DI SDN BANYUKAMBANG - Vivi Klara Dhistha; Nita Ayu Saputri; Venus Sandro Marosgun; Dewi Tryanasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Digital technology development requires the education sector to adapt through innovative learning media to enhance effectiveness and student engagement. This community service activity aims to improve teacher competence in utilizing digital teaching media and enhance students' literacy and numeracy skills at SDN Banyukambang, Madiun Regency. The primary issue identified was the underutilization of available digital facilities, such as Smart TVs and LCDs, where teachers still predominantly used conventional lecture methods, resulting in low student learning motivation. The implementation method consisted of three main stages: (1) Observation to identify learning needs and obstacles; (2) Training and Mentoring in creating teaching media using the Canva application and the Wordwall interactive platform ; and (3) Media Implementation directly within the teaching and learning process for grades II and III. The results of the activity showed a significant increase in teachers' pedagogical competence in developing varied and interactive learning media. For students, the application of Wordwall had a positive impact by increasing enthusiasm, motivation, and active participation, which led to improved literacy and numeracy learning outcomes. This activity successfully created synergy between the university and the school in supporting digital-based educational transformation relevant to 21st-century demands.